BIOMASSA SESAAT SUMBER DAYA PERIKANAN UNDUR-UNDUR LAUT (CRUSTACEA: DECAPODA: HIPPIDAE) DI PANTAI BERPASIR CILACAP DAN KEBUMEN, JAWA TENGAH - Ali Mahsar; Yusli Wardiatno (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2016)
ABSTRACTMole crab is a benthic animal that live buried in sandy beach in the intertidal area. Mole crab has  an  important  ecological  role  and  also  has  economic  value.  The  sandy  beach  in  south  of Cilacap  and  Kebumen  is  mole  crab’s  habitat.  Mole  crab  exploitation  in  these  areas  has  been increasing  for  consumption  demand.  To  determine  the  significant  role  of  the  mole  crab  in  the provision  of  nutritious  food,  it  is  necessary  to  estimate  the  potential  of  mole  crab  biomass.  This study  aims  to  determine  standing  biomass  of  the  mole  crab  in  Kebumen  and  Cilacap  sandy beaches.  The  specimen  collection  was  conducted  by  sampling  methods  every  month  in  March 2012 to February 2013 on Bocor beach, Kebumen and June 2013 to May 2014 on Bunton beach, Cilacap. The data processing was conducted by descriptive statistics methods. The results showed that standing biomass of mole crab family Hippidae, namely Emerita emeritus and Hippa adactyla, fluctuated between 102 and 508 kg on the Kebumen sandy beach, and between 1,811 and 4,671 kg on the Cilacap sandy beach. Standing biomass of E. emeritus fluctuated between 82 and 497 kg on  the  Kebumen  sandy  beach  and  between  1,462  and  3,560  kg  on  the  Cilacap  sandy  beach.Standing biomass of H. adactyla fluctuated between 2 and 133 kg on the Kebumen sandy beach, and between 234 and 1,701 kg on the Cilacap sandy beach. The difference in standing biomass in each  location  was  caused  by  the  difference  of  sampling  time  and  environment  condition  of research area. The economic value potential of the mole crab as fishery resources is discussed.Keywords: Emerita emeritus, Hippa adactyla, Hippidae, momentarily biomass,ABSTRAKUndur-undur laut adalah kelompok hewan bentik yang hidup  mengubur di daerah intertidal bersusbtrat pasir. Undur-undur laut mempunyai peran ekologis penting dan juga bernilai ekonomis. Pantai  berpasir  selatan  Cilacap  dan  Kebumen  adalah  habitat  undur-undur  laut.  Penangkapan undur-undur  laut  di  kedua  wilayah  tersebut  makin  meningkat  untuk  kebutuhan  konsumsi.  Untuk mengetahui  peran  undur-undur  laut  dalam  mendukung  penyediaan  bahan  pangan  bergizi,  perlu diketahui potensi biomassa undur-undur laut. Penelitian ini bertujuan untuk mengetahui biomassa sesaat  undur-undur  laut  dan  fluktuasinya  di  pantai  berpasir  Kabupaten  Kebumen  dan  Cilacap. Pengumpulan  spesimen  undur-undur  laut  dilakukan  dengan  metode  sampling  setiap  bulan  pada Maret 2012 hingga Februari 2013 di pantai Bocor Kebumen dan pada Juni 2013 hingga Mei 2014 di  pantai  Bunton  Cilacap.  Pengolahan  data  dilakukan  dengan  metode  statistik  deskriptif.  Hasil penelitian  menunjukkan  bahwa  besaran  biomassa  sesaat  (standing  biomass)  undur-undur  laut famili Hippidae, yaitu  Emerita emeritus  dan  Hippa adactyla, berfluktuasi  antara 102 kg hingga 508 kg di pantai berpasir Kebumen, dan antara 1.811 kg hingga 4.671 kg di pantai berpasir Cilacap. Standing biomass E. emeritus berfluktuasi antara 82 kg hingga 497 kg di pantai berpasir Kebumen dan  antara  1.462  kg  hingga  3.560  kg  di  pantai  berpasir  Cilacap.  Standing  biomass  H.  adactylaberkisar antara 2 kg hingga 133 kg di pantai berpasir Kebumen, dan antara 234 kg hingga 1.701 kg di  pantai  berpasir  Cilacap.  Perbedaan  besaran  standing  biomass  di  masing-masing  lokasi dipengaruhi  oleh  perbedaan  waktu  pengumpulan  data  undur-undur  laut  dan  perbedaan  kondisi lingkungan  lokasi  penelitian.  Potensi  ekonomi  sebagai  sumber  daya  perikanan  undur -undur  laut juga dibahas dalam paper ini.Kata kunci: Emerita emeritus, Hippa adactyla, Hippidae, biomassa sesaat